Interpreting Reports From Universal Screeners: Roadblocks, Solutions, and Implications for Designing Score Reports - Shivraj, Pooja; Ketterlin-Geller, Leanne R. (Frontiers in Education, 2019)
Many teachers struggle with interpreting formative assessment data. As a result, they are often unable to modify instruction that is responsive to student performance. To support valid interpretations and uses of assessments, test developers need to better understand teachers’ ability to read and interpret score reports, their perception of the information that is being conveyed, and how they use the information to change instruction. The purpose of this manuscript is to report on a series of focus groups examining (a) how teachers interact with various score report features and (b) how these features support or hinder their ability to interpret and analyze formative assessment data. Results provide insights into the design of score reports that may facilitate teachers’ ability to interpret and analyze data and, ultimately, use these data to modify their instruction to improve student outcomes. Solutions to the roadblocks teachers encountered are proposed and generalized examples of how score reports can be designed to facilitate teachers’ interpretations are provided. Findings from this study may help test developers anticipate challenges the intended audience could face when interpreting assessment results on score reports, and subsequently improve the quality of score reports to enhance teachers’ interpretations and decision-making at the classroom level.